Investigating Manuka Honey Antibacterial Properties When Incorporated into Cryogel, Hydrogel, and Electrospun Tissue Engineering Scaffolds - Katherine R. Hixon; Savannah J. Bogner; Gabriela Ronning-Arnesen; Blythe E. Janowiak; Scott A. Sell (Gels, 2019)
Honey is well-known for its wound healing capability and Manuka honey (MH) contains a unique Manuka factor, providing an additional antibacterial agent. Previously, there has not been a practical way to apply MH to a wound site, which renders treatment for an extended period extremely difficult. Tissue-engineered scaffolds offer an alternative treatment method to standard dressings by providing varying geometries to best treat the specific tissue. MH was incorporated into cryogels, hydrogels, and electrospun scaffolds to assess the effect of scaffold geometry on bacterial clearance and adhesion, as well as cellular adhesion. Electrospun scaffolds exhibited a faster release due to the nanoporous fibrous geometry which led to a larger partial bacterial clearance as compared to the more three-dimensional cryogels (CG) and hydrogels (HG). Similarly, the fast release of MH from the electrospun scaffolds resulted in reduced bacterial adhesion. Overall, the fast MH release of the electrospun scaffolds versus the extended release of the HG and CG scaffolds provides differences in cellular/bacterial adhesion and advantages for both short and long-term applications, respectively. This manuscript provides a comparison of the scaffold pore structures as well as bacterial and cellular properties, providing information regarding the relationship between varying scaffold geometry and MH efficacy.